A Three-Layer Oniom Model for the Outside Binding of Cationic Porphyrins and Nucleotide Pair Dna - Cardenas-Jiron, G; Cortez-Santibanez, L (2013)
In this work we investigated the outside binding mode between a cationic porphyrin and a nucleotide pair of DNA, adenine-thymine and guanine-cytosine, in a supramolecular assembly. We used two structural models (semi-extended, extended) that differ in the size of porphyrin, two kinds of theoretical methods: a three layer ONIOM (B3LYP/6-31G(d)/PM3/UFF), and DFT B3LYP/6-31G(d,p), and three cationic porphyrins. ONIOM method was first tested on the semi-extended model that was calculated in four environments: gas phase, solution phase using an explicit solvent model (H2O), in the presence of a sodium cation (Na+) and in both (H2O + Na +). From interaction energy results, we found that the affinity of the cationic substituent by the adenine nucleotide is favored upon the thymine nucleotide. The extended model that considers the whole porphyrin was applied in the gas phase to the four nucleotides. All the cationic porphyrins showed affinity by the nucleotides in the order adenine > guanine > thymine > cytosine. The interaction energy values for outside binding showed a strong porphyrin-nucleotide interaction (?-90 kcal mol-1), that slightly varies between the nucleotides suggesting that this kind of cationic porphyrin has a little selectivity for some of them. We also found that the effect of the nature of the cationic substituent (chain length) in the porphyrin on the outside binding is small (?2-13 kcal mol-1). Coherence between the results showed that ONIOM is a useful tool to get a reasonable molecular geometry to be used as a starting point in calculations of density functional theory. [Figure not available: see fulltext.] © 2012 Springer-Verlag Berlin Heidelberg.